\(4\left(3x^2-4\right)-6\left(2x^2-2x\right)=-16\)

K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

11 tháng 10 2018

4(3x2-4)-6(2x2-2x)=-16

12x2-16-12x2+12x=-16

12x2-12x2+12x=16-16

12x=0

=>x=0

11 tháng 10 2018

\(4\left(3x^2-4\right)-6\left(2x^2-2x\right)=-16.\)

\(12x^2-16-12x^2+12x=-16\)

\(12x^2-12x^2+12x=16-16\)

\(12x=0\)

Học tốt

1) \(\left(x+2y\right)^2=x^2+4xy+4y^2\)

2) \(\left(2x+3y\right)^2=4x^2+12xy+9y^2\)

3) \(\left(x+\frac{1}{3}\right)^4=\left[\left(x+\frac{1}{3}\right)^2\right]^2=\left(x^2+\frac{2}{3}x+\frac{1}{9}\right)^2=x^4+\frac{4}{9}x^2+\frac{1}{81}+\frac{4}{3}x^3+\frac{4}{27}x+\frac{2}{9}x^2=x^4+\frac{2}{3}x^2+\frac{1}{81}+\frac{4}{3}x^3+\frac{4}{27}x\)

4) \(\left(2x+y^2\right)^3=8x^3+12x^2y^2+6xy^4+y^6\)

5) Sửa đề: \(\left(\frac{x}{2}-2y\right)^3=\frac{x^3}{8}-\frac{3x^2}{2}+6xy^2-8y^3\)

6) \(\left(\sqrt{2x-y}\right)^4=\left(2x-y\right)^2=4x^2-4xy+y^2\)

7) \(\left(x+1\right)\left(x^2-x+1\right)=x^3+1\)

8) \(\left(x-3\right)\left(x^2+3x+9\right)=x^3-27\)

a: \(=\dfrac{27a^6b^3\cdot a^2b^6}{a^8b^8}=27b\)

b: \(=3y^2-5x^2y^3-2y^2+3x^2y^3\)

\(=y^2-2x^2y^3\)

c: \(=6x-y+2x^2+3y-2x^2+x\)

\(=7x+2y\)

d: \(=x-y+2y^2-6xy+\dfrac{10x^2}{y}\)

a: \(=3y^2-5x^2y^3-2y^2+3x^2y^3=y^2-2x^2y^3\)

b: \(=6x-y+2x^2+3y^2-2x^2+x=7x-y+3y^2\)

c: \(=x-y+4y^2-6xy+\dfrac{10x^2}{y}\)

 

23 tháng 9 2018

\(a.\left(9x^2y^3-15x^4y^4\right):3x^2y-\left(2-3x^2y\right)y^2\)

\(=3y^2-5x^2y^3-2y^2+3x^2y^3\)

\(=y^2-2x^2y^3\)

\(b.\left(6x^2-xy\right):x+\left(2x^3y+3xy^2\right):xy-\left(2x-1\right)x\)

\(=6x-y+2x^2+3y-2+x\)

\(=2x^2+7x+2y-2\)

\(c.\left(x^2-xy\right):x+\left(6x^2y^5-9x^3y^4+15x^4y^3\right):\dfrac{3}{2}x^2y^3\)

\(=x-y+4y^2-6xy+10x^2\)

23 tháng 9 2018

Oa, giờ mới biết bác cũng ở box Toán :))

17 tháng 5 2019

A= 3xy-11x2-5y.8xy-5+6

=(3-11-5.8-5+6).(x2.x2.x).(y.y.y)

=-47x5y3

a) Ta có: \(\left(x-3\right)\left(x^2+3x+9\right)\)

\(=\left(x-3\right)\left(x^2+x\cdot3+3^2\right)\)

\(=x^3-3^3=x^3-27\)

b) Ta có: \(\left(x-2\right)\left(x^2+2x+4\right)\)

\(=\left(x-2\right)\left(x^2+x\cdot2+2^2\right)\)

\(=x^3-2^3=x^3-8\)

c) Ta có: \(\left(x+4\right)\left(x^2-4x+16\right)\)

\(=\left(x+4\right)\left(x^2-x\cdot4+4^2\right)\)

\(=x^3+4^3=x^3+64\)

d) Ta có: \(\left(x-3y\right)\left(x^2+3xy+9y^2\right)\)

\(=\left(x-3y\right)\left[x^2+x\cdot3y+\left(3y\right)^2\right]\)

\(=x^3-\left(3y\right)^3=x^3-27y^3\)

e) Ta có: \(\left(x^2-\frac{1}{3}\right)\left(x^4+\frac{1}{3}x^2+\frac{1}{9}\right)\)

\(=\left(x^2-\frac{1}{3}\right)\left[\left(x^2\right)^2+x^2\cdot\frac{1}{3}+\left(\frac{1}{3}\right)^2\right]\)

\(=\left(x^2\right)^3-\left(\frac{1}{3}\right)^3\)

\(=x^6-\frac{1}{27}\)

f) Ta có: \(\left(\frac{1}{3}x+2y\right)\left(\frac{1}{9}x^2-\frac{2}{3}xy+4y^2\right)\)

\(=\left(\frac{1}{3}x+2y\right)\left[\left(\frac{1}{3}x\right)^2-\frac{1}{3}x\cdot2y+\left(2y\right)^2\right]\)

\(=\left(\frac{1}{3}x\right)^3+\left(2y\right)^3\)

\(=\frac{1}{27}x^3+8y^3\)